2003
DOI: 10.1128/jcm.41.5.2258-2260.2003
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum Transmission of Penicillin-Resistant Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is a rarely recognized cause of neonatal sepsis. We present a recent case of S. pneumoniae bacteremia acquired on the first day of life in a neonate born at 30 weeks of gestation to a mother without prenatal care who had prolonged rupture of the membranes and received intravenous ampicillin prior to delivery. The isolate was resistant to penicillin, with a MIC of the drug of 4 g/ml. The child responded to a 7-day course of intravenous vancomycin. S. pneumoniae was recovered from the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
0
22
0
5
Order By: Relevance
“…39 It has been suggested that maternal vaginal colonization with S. pneumoniae may be responsible for its peripartum transmission. 40,41 and may be an important mode of spread of S. pneumoniae in developing countries. In contrast to the WHO young infant study, which enrolled infants up to 90 days of age, our study included only infants below 60 days old.…”
Section: Discussionmentioning
confidence: 99%
“…39 It has been suggested that maternal vaginal colonization with S. pneumoniae may be responsible for its peripartum transmission. 40,41 and may be an important mode of spread of S. pneumoniae in developing countries. In contrast to the WHO young infant study, which enrolled infants up to 90 days of age, our study included only infants below 60 days old.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, McDonald and colleagues reported a case of S. pneumoniae bacteremia acquired on the first day of life in a premature baby. 15 The isolate was resistant to penicillin with an MIC of 4 µg/mL and intermediately susceptible to cefotaxime and ceftriaxone, both MIC = 1.0 µg/mL. The baby responded well to vancomycin.…”
Section: Discussionmentioning
confidence: 94%
“…En la patogenia de la infección invasora del RN por S. pneumoniae se ha atribuido un rol a la transmisión vertical asociada a portación vaginal materna y/o a endometritis 2,5,6 . Mediante estudios de biología molecular se ha comprobado la transmisión clonal de la bacteria desde la madre al niño 5 .…”
Section: Discussionunclassified
“…Mediante estudios de biología molecular se ha comprobado la transmisión clonal de la bacteria desde la madre al niño 5 . La frecuencia de colonización vaginal por S. pneumoniae es muy baja (< 0,03%), sugiriendo una alta incidencia de infección invasora en el RN expuesto a este agente durante el parto 2 .…”
Section: Discussionunclassified
See 1 more Smart Citation